A proteção do trabalho decente nas plataformas digitais : caminhos para a garantia da efetividade dos direitos humanos e fundamentais - Santana Filho, José Ricardo de (2023)
The advances resulting from the development of new information and communication technologies are causing major changes in society, either in the way of relating and doing business, or in the way of working. In parallel, capitalism undergoes transformations and changes in its practices, with the emergence of practices associated with the economy of sharing goods and services, a trend that allows each person to be consumers and producers at the same time. New companies that use these elements in their business models – digital platforms – generate new challenges and perspectives for modern working relationships. Faced with the diffusion of the thought that each one can be the entrepreneur of himself and to manage his own activities, there is a deconstruction of the employment relationship and the loss of social rights. In a broader perspective, it is seen that these circumstances are the product of a tendency to informality, in which workers are transformed into just-in-time workers. The problem that is a concern of this research is whether it is possible to reconcile technological advances with the guarantee of workers' human rights in the face of industry 4.0. In this view, the paper discusses how to ensure the effectiveness of human rights within a context of a precarious digital economy. It is observed that from the shared economy and work through digital platforms new social relationships emerge that do not implement the essential rights of workers. Therefore, it is necessary to reconcile labor human rights with the development of new trends in the platform economy. Thus, it was found that, among the available alternatives, the creation of a special contract through specific regulation is more efficient to ensure the effectiveness of labor human rights in the new labor relations that arise from digital platforms, considering that it adapts the protective instrument to the new technological reality of modern times.